The expression of MALAT1, plasma brain natriuretic peptide, and Tei index in sepsis-induced myocardial injury - Guangqing Huang; Wenzi Yang; Xu Zhao; Yong Bai; Xing Jiang; Jie Liu (Journal of Cardiothoracic Surgery)
Abstract Purpose We sought to investigate the expression of MALAT1, plasma brain natriuretic peptide, and Tei index in sepsis-induced myocardial injury. Methods The current retrospective analysis focused on 146 sepsis patients admitted to our hospital from February 2021 to March 2023. Based on the presence or absence of myocardial injury, the patients were divided into two groups: the sepsis group (n = 80) and the sepsis-induced myocardial injury group (n = 66). Based on the 28-day mortality status of the patients, they were also divided into a survival group of 143 cases and a death group of 3 cases. The study compared the levels of MALAT1, plasma brain natriuretic peptide, and Tei index between the sepsis group and sepsis-induced myocardial injury group, as well as the comparison of two sets of ultrasound indicators. Univariate logistic regression analysis was performed to identify the influencing factors of sepsis-induced myocardial injury, followed by multivariate logistic regression analysis to identify the influencing factors of such condition. MALAT1, plasma brain natriuretic peptide and cardiac Tei index between the survival and death groups were compared and Pearson correlation analysis was conduct to assess their correlations. Results In terms of general information, there were no significant differences in gender, age, BMI, mean arterial pressure, systolic pressure, diastolic pressure, respiratory rate, oxygenation index, basic diseases and infection site between the two groups (P > 0.05). However, significant differences were observed in heart rate, SOFA score, and APACHE II score between the two groups (P < 0.05). The levels of MALAT1, plasma brain natriuretic peptide, and Tei index in the sepsis-induced myocardial injury group were significantly higher than those in the sepsis group (P < 0.05). Furthermore, the sepsis-induced myocardial injury group exhibited lower left ventricular end-diastolic diameter and left ventricular end-systolic diameter compared to the sepsis group, along with higher levels of E, E/e’, and e’, showing significant differences (P < 0.05). The independent variables considered in the analysis included general data, ultrasound indicators with significant differences, as well as MALAT1, plasma brain natriuretic peptide, and Tei index. The dependent variable was sepsis-induced myocardial injury, and univariate logistic regression analysis identified E, E/e’, e’, MALAT1, plasma brain natriuretic peptide, and Tei index as influencing factors of sepsis-induced myocardial injury. Subsequently, a multivariate logistic regression analysis was conducted with the independent variables set as E, E/e’, e’, MALAT1, plasma brain natriuretic peptide, and Tei index, and the dependent variable as sepsis-induced myocardial injury. The results indicated that MALAT1, plasma brain natriuretic peptide, and Tei index were influencing factors of sepsis-induced myocardial injury. The levels of MALAT1, plasma brain natriuretic peptide and cardiac Tei index in the death group were significantly higher than those in the survival group (P < 0.05). The Pearson correlation analysis showed that MALAT1, plasma brain natriuretic peptide and cardiac Tei index were correlated with the prognosis of patients with sepsis-induced myocardial injury (P < 0.05). Conclusion We demonstrated high expression levels of MALAT1, plasma brain natriuretic peptide, and Tei index in patients with sepsis-induced myocardial injury. Ultrasound indicators can effectively contribute to the diagnosis of sepsis-induced myocardial injury. Moreover, MALAT1, plasma brain natriuretic peptide, and Tei index have been identified as influencing factors of sepsis-induced myocardial injury.